2021
DOI: 10.1111/and.14126
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera ethanolic extract ameliorates the testicular dysfunction resulted from HFD‐induced obesity rat model

Abstract: In this study, we estimated the protective role of Moringa oleifera leaf ethanolic extract (MOLE) against obesity‐associated testicular dysfunction. Fifty male albino rats were randomly assigned to five groups (n = 10): Group I (basal diet), group II (basal diet plus MOLE orally), group III (high‐fat diet—HFD), group IV (HFD plus oral MOLE) and group V (HFD for 8 weeks followed by a basal diet plus oral MOLE for 6 weeks). The study duration extended for 14 weeks. Serum collected to investigate testosterone, FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…The combination of obesity and diabetes has been shown to hurt various aspects of sperm quality as well as hormone levels and testicular health, as observed in the study by Alkafafy et al (2021). These results are similar to previous studies using obese and diabetic rat models.…”
Section: Discussionsupporting
confidence: 90%
“…The combination of obesity and diabetes has been shown to hurt various aspects of sperm quality as well as hormone levels and testicular health, as observed in the study by Alkafafy et al (2021). These results are similar to previous studies using obese and diabetic rat models.…”
Section: Discussionsupporting
confidence: 90%
“… 23 The modeling method of HFD is similar to the formation principle of dyslipidemia caused by human diet, and the modeling method is convenient, which is the common method of fat modeling animals at present. 24 , 25 This study found that elevated serum levels of TC, TG, and LDL-C can lead to endothelial dysfunction, which is closely related to ED. The ICP/MAP data showed that there was a statistically significant difference between the ICP/MAP ratios of the ED and IL-18 groups and the control group.…”
Section: Discussionmentioning
confidence: 77%
“…Alkafafy et al showed that ethanolic extract of Moringa leaves at 300 mg/kg improved mouse testicular dysfunction with a high-fat diet-induced obesity model, which was indicated by enhancement in testosterone hormone, LH, and FSH levels. The results showed that there was a decrease in degenerative changes in spermatogenic cells along with an increase in cell count and sperm motility 30 . Jannah et al reported that rats who had diabetes mellitus experienced histopathological improvement after the administration of ethanolic extract of Moringa leaves at 200 mg/kg, 300 mg/kg, 400 mg/kg, and 500 mg/kg doses, with the best histopathological structure observed at 400 mg/kg.…”
Section: Effect Of Moringa Leaves Ethanolic Extract On Testicular His...mentioning
confidence: 93%